Adherence and safety study in patients on treatment with capecitabine - Francisca Fernández-Ribeiro; Rosario Olivera-Fernández; Carlos Crespo-Diz (Elsevier, 2017)
Background: The introduction of oral antineoplastic agents in therapeutics has caused a change in the treatment strategy against cancer. The objective of this study was to analyze the adherence in patients to treatment with capecitabine, their adverse events, and the overall health status of patients, as well as the relationship of these factors with adherence. Method: An observational, prospective study at 7 months, in a cohort of patients on capecitabine treatment, including treatment initiations and continuations, regardless of diagnosis or indication. The data collected were: demographic variables (age, gender), diagnostic (breast cancer, colorectal cancer, gastric cancer, off-label), adherence (tablet count, Morisky test, Sackett test), safety (assessment of adverse events, clinical evaluation by the oncologist) and quality of life (performance status, SF-12 test). Data sources: electronic clinical records (IANUS®), dispensing program for outpatients (SILICON®) and interviews with patients. Results: There were 111 evaluable patients, with a mean age of 66.7 years (range 32-86), ECOG PS 1 in 76.6%. Adherence level: 78.4% (81.7% in the initiation sub-group vs. 72.5% in the continuation sub-group). Adverse events: skin toxicity (33.33%), asthenia (25.22%), gastrointestinal toxicity (24.32%) and neurological toxicity (24.32%), mostly G1. Health status, SF-12 test: subjective evaluation as "good" in 33.30% of cases. Conclusions: The low level of adherence in the continuation sub-group can be associated with the duration of treatment, toxicities, clinical evolution, and perception of their health status. It is necessary to conduct individualized monitoring in this group of patients in order to obtain a favorable clinical response.